Compression Stockings for Treating Venous Leg Ulcers. (3rd February 2013) - Benigni, J. P.; Deman, A. L.; Uhl, J. F.
Abstract : Background . In order to treat venous leg ulcers, it is recommended to use high pressure compression (30–40 mmHg at the ankle). Compression stockings which are not operator dependant could be the best option because of their pressure control. However 30–40 mmHg compression stockings are often hard to put on. Putting two lower pressure compression stockings over each other could be a good therapeutic alternative. Objectives . To compare the in vitro pressures given by the manufacturers of 2 antiulcer kits with the in vivo interface pressures measured in healthy subjects and to evaluate the stiffness and friction indices from those kits based on the interface pressure in order to assess their clinical properties. Material and Methods . Using a Kikuhime pressure device, interface pressure was measured in 12 healthy subjects at the reference point B1. One stiffness index (Static Stiffness Index (SSI)) and a friction index have been calculated. Results . Mediven Ulcer kit gets the recommended pressures whereas Jobst's Ulcer Care kit does not for treating a venous leg ulcer. Jobst's Ulcer Care transmits entirely the pressure in relation to a friction index close to 1. Conclusion . This antiulcer kit study underlines that in vivo and in vitro pressures can be different (Jobst's Ulcer Care kit and Mediven Ulcer kit). In order not to lose pressure, it is important to take into account the friction index when superimposing two stockings.